2008
DOI: 10.1161/strokeaha.107.504019
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-From the studied variables in subarachnoid hemorrhage (SAH) risk, hypertension is probably the most controvertible one. The aim of this study was to determine whether confirmed hypertension, prospectively diagnosed with strict criteria, is an independent risk factor for aneurysmal SAH. Methods-A case-control study was conducted in 2 colombian cities between July 2004 and June 2005. There were 163 new cases of SAH (mean age 51 years; 107 were women) with 2 controls per case: 1 hospital an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…A Colombian case-control study found no significant association between coffee intake and SAH. 12 Our results appear to be consistent with those of a Norwegian study 11 that showed significantly increased SAH mortality among subjects who drank more than 6 cups of coffee a day.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A Colombian case-control study found no significant association between coffee intake and SAH. 12 Our results appear to be consistent with those of a Norwegian study 11 that showed significantly increased SAH mortality among subjects who drank more than 6 cups of coffee a day.…”
Section: Discussionsupporting
confidence: 91%
“…To our knowledge, this is the first report of a significant increase of SAH incidence among heavy coffee drinkers in Japan. Given the mixed epidemiological research results on the cerebrovascular effects of coffee, 5 7 , 11 , 12 , 16 this finding is valuable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among patients with aSAH, 60% were hypertensive. Hypertension is an independent risk factor for aSAH, [21][22][23] and Asian descents are more prone to hypertension compared with Caucasians. [24][25][26] In the Philippines, it is the leading cardiovascular disease at 38%.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data upon which to make dietary recommendations specifically for the prevention of subarachnoid hemorrhage (SAH) in high-risk individuals [20,21,22,23,24,25,26,27]. There may be specific dietary exposure that alone or in association with the two established risk factors for the condition, namely hypertension and smoking, may contribute to the formation and rupture of intracranial aneurysms.…”
Section: Introductionmentioning
confidence: 99%